Svad'ba tishiny - Medvedev, Pavel (Russia, 2003)
A film about people who live in a world of silence. A mother doesn’t hear the voices of her children, nor men the din of the foundry where they work. But still they lead full lives. They enjoy family gatherings immensely and love to dance. At church the priest imparts his message by means of sign language, their eyes perceiving the beauty of the liturgy. Even the wedding of a couple from the deaf community proceeds like any other – champagne sparkles in silence, hands create magical toasts. The next day the new husband and his co-workers are back at the foundry casting an enormous bell in honour of Petersburg’s 300th anniversary – they admire their work but won’t hear its sonorous sound as it tolls for the celebration.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films